MODERNIZATION AND MEDIA IN SAUDI ARABIA: A CONCEPTUAL PSYCHOMETRIC FRAMEWORK FOR UNDERSTANDING RELIGIOUS-CULTURAL IDENTITY TRANSFORMATION UNDER VISION 2030 - MANAL MAGDY MOHAMMED HASSAN, UDAYA NARAYANA SINGH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This paper proposes a conceptual psychometric framework to examine the psychosocial dynamics of modernization in Saudi Arabia under Vision 2030. Moving beyond economic and political interpretations, modernization is conceptualized as a measurable construct reflecting the cognitive and affective processes through which individuals reconcile media-driven change with religious-cultural identity. Drawing from Social Identity Theory, Cultural Tightness–Looseness, and the Uses and Gratifications approach, this proposal introduces the Media-Driven Modernization Attitudes Scale (MDMAS). The framework theorizes that media engagement influences acceptance of modernization through perceived compatibility between religiosity and modernity, moderated by national identity salience and gender. The study integrates psychometric principles—construct validity, measurement equivalence, and factor structure—into a culturally specific context rarely examined in applied psychology. By treating modernization as an operationalizable psychological variable, this conceptual model provides a methodological foundation for future testing, cross-cultural validation, and policy-oriented research. The proposed framework advances applied psychology by linking sociocultural transformation to measurable dimensions of attitude, belief, and identity negotiation.